Polyethylene glycol 3350 plus electrolytes for chronic constipation in children: a double blind, placebo controlled, crossover study. Issue 11 (11th July 2007) - Thomson, M A; Jenkins, H R; Bisset, W M; Heuschkel, R; Kalra, D S; Green, M R; Wilson, D C; Geraint, M
Abstract : Objectives: To assess the efficacy and safety of polyethylene glycol 3350 plus electrolytes (PEG+E) for the treatment of chronic constipation in children. Design: Randomised, double blind, placebo controlled crossover trial, with two 2-week treatment periods separated by a 2-week placebo washout. Setting: Six UK paediatric departments. Participants: 51 children (29 girls, 22 boys) aged 24 months to 11 years with chronic constipation (lasting ⩾3 months), defined as ⩽2 complete bowel movements per week and one of the following: pain on defaecation on 25% of days; ⩾25% of bowel movements with straining; ⩾25% of bowel movements with hard/lumpy stools. 47 children completed the double blind treatment. Main outcome measures: Number of complete defaecations per week (primary efficacy variable), total number of complete and incomplete defaecations per week, pain on defaecation, straining on defaecation, faecal incontinence, stool consistency, global assessment of treatment, adverse events and physical examination. Results: The mean number of complete defaecations per week was significantly higher for children on PEG+E than on placebo (3.12 (SD 2.05) v 1.45 (SD 1.20), respectively; p<0.001). Further significant differences in favour of PEG+E were observed for total number of defaecations per week (p = 0.003), pain on defaecation (p = 0.041), straining on defaecation (p<0.001), stool consistency (p<0.001) and percentage of hard stools (p = 0.001). Treatment related adverse events (all mild or moderate) occurred in similar numbers of children on PEG+E (41%) and placebo during treatment (45%). Conclusions: PEG+E is significantly more effective than placebo, and appears to be safe and well tolerated in the treatment of chronic constipation in children.